Pedagogical practices in Higher Education: what do scientific-academic productions report between 2020 and 2021? (Research, Society and Development, 2022)
Pedagogical practices are actions that occur in the educational scenario from Basic Education to Higher Education in order to develop the teaching and learning processes. Several pedagogical practices can be studied, such as: planning, teaching method, evaluation, internships, initiation to teaching, however, in this study the focus is directed to Higher Education. From the problematization that involves the importance of pedagogical practices, the insertion of practices in undergraduate courses and the connection between pedagogical practices and inclusion, the objective of this work is to evaluate the scientific-academic productions between 2020 and 2021 in the context of pedagogical practices in the University education. In the meantime, an exploratory bibliographic research of a qualitative nature was carried out, seeking to evaluate the concentrations of pedagogical practices in Higher Education courses. The data were analyzed in the light of Bardin (2006) in two categories covering the following topics: Pedagogical training, planning and teaching methodologies and Information and Communication Technologies. The results point to the lack of ICT in the mediation of pedagogical practices of higher education teachers in the teaching and learning process, as the analyzed studies raise the importance of practice as a social articulation in universities and how the development of practices is satisfactory between students and teachers when it occurs adopting the perspective of innovation and updating of teaching methodologies.